2015
DOI: 10.1083/jcb.201411037
|View full text |Cite|
|
Sign up to set email alerts
|

Endocytosis-dependent coordination of multiple actin regulators is required for wound healing

Abstract: Live imaging of epidermal wound closure in Drosophila embryos reveals that assembly of motile F-actin at wound edges requires the endocytic remodeling of adherens junctions and is mediated by Diaphanous, SCAR, and WASp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 64 publications
(86 reference statements)
2
29
1
Order By: Relevance
“…The formation of the actomyosin cable depends on remodeling of the Adherens Junctions (AJs) (Abreu-Blanco et al, 2012; Carvalho et al, 2014; Hunter et al, 2015; Matsubayashi et al, 2015). After wounding, the AJ protein E-cadherin (E-cad) is downregulated at the cell boundaries facing the wound, remaining only at the lateral junctions of leading-edge cells.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the actomyosin cable depends on remodeling of the Adherens Junctions (AJs) (Abreu-Blanco et al, 2012; Carvalho et al, 2014; Hunter et al, 2015; Matsubayashi et al, 2015). After wounding, the AJ protein E-cadherin (E-cad) is downregulated at the cell boundaries facing the wound, remaining only at the lateral junctions of leading-edge cells.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Abl loss has a similar effect, and in the case of Abl its loss impairs both actin organization at the wound edge and enrichment of the cadherin-catenin complex at tricellular junctions (Zulueta-Coarasa et al, 2014). SCAR is also critical for embryonic wound healing (Matsubayashi et al, 2015). In the future it will be important to explore which cell biological events required for wound healing are regulated by Crk.…”
Section: Crk Plays Additional Roles In the Central Nervous System Andmentioning
confidence: 99%
“…dl regulation is impaired during closure in Grh KD We next investigated how Grh loss-of-function impairs E-Cad dynamics during wounding and, thus, the repair process. It has been shown that, in Drosophila embryos, the downregulation and turnover of E-Cad at the AJs is required for actin polymerization and bundle formation, leading to the assembly of the contractile cable around the wound margin (Carvalho et al, 2014;Hunter et al, 2015;Matsubayashi et al, 2015). Moreover, the Toll-NF-κB signaling pathway is required for E-Cad turnover during wound closure.…”
Section: E-cad Establishes a Link Between Cell Adhesion And Cytoskeletonmentioning
confidence: 99%
“…E-Cad turnover and recycling are important in accommodating cell shape changes, as well as actomyosin flow formation and directionality (Antunes et al, 2013;Pinheiro et al, 2017;Rauzi et al, 2010). It has recently been shown in Drosophila embryos that inhibition of E-Cad turnover leads to an impairment in actin cable formation and wound closure (Carvalho et al, 2014;Hunter et al, 2015;Matsubayashi et al, 2015). However, it is still unknown how E-Cad is regulated during wound repair.…”
Section: Introductionmentioning
confidence: 99%